The Expanding Arsenal of Cytotoxic T Cells - Cassioli, Chiara; Baldari, Cosima T. (Frontiers in Immunology, 2022)
Cytotoxic T cells (CTLs) are the main cellular mediators of the adaptive immune defenses against intracellular pathogens and malignant cells. Upon recognition of specific antigen on their cellular target, CTLs assemble an immunological synapse where they mobilise their killing machinery that is released into the synaptic cleft to orchestrate the demise of their cell target. The arsenal of CTLs is stored in lysosome-like organelles that undergo exocytosis in response to signals triggered by the T cell antigen receptor following antigen recognition. These organelles include lytic granules carrying a cargo of cytotoxic proteins packed on a proteoglycan scaffold, multivesicular bodies carrying the death receptor ligand FasL, and the recently discovered supramolecular attack particles that carry a core of cytotoxic proteins encased in a non-membranous glycoprotein shell. Here we will briefly review the main features of these killing entities and discuss their interrelationship and interplay in CTL-mediated killing.